Alumina nanoflake‐coated graphene nanohybrid as a novel flame retardant filler for polypropylene. (28th June 2019) - Yuan, Bihe; Chen, Gongqing; Zou, Yanyan; Shang, Sheng; Sun, Yaru; Yu, Bin; He, Song; Chen, Xianfeng
Abstract : γ‐Al2 O3 nanoflakes are decorated on the surface of graphene nanosheets by hydrothermal method. The chemical structures, composition, and morphology of the graphene nanohybrid are characterized. Alumina nanoflake‐coated graphene nanohybrid is incorporated into polypropylene (PP) matrix by master batch‐based melt mixing method. The effects of alumina‐graphene nanohybrid on the thermal stability and combustion behavior of PP are investigated. More char residue is left for PP composite containing alumina‐graphene nanohybrid. Peak heat release rate of pure PP is greatly decreased by this nanohybrid, corresponding to 30.6% reduction. Fire safety of PP is considerably enhanced. Flame retardant mechanisms are concluded based on the combustion results and char analysis. The barrier effect of graphene and catalytic charring actions of γ‐Al2 O3 nanoflakes make the contribution to the enhanced flame retardant properties.